THE EFFECT OF MSME TAX REDUCTION AND TAX SANCTIONS ON TAXPAYER COMPLIANCE FOR MSMES IN SHOES CAMPOENG IN SIDOARJO - Risaldif Kleventura; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
The government has completed the revision of Government Regulation Number 46 of 2013 which is the legal basis for imposing tariffs for taxpayers (WP) micro, small and medium enterprises (MSMEs), which is 0.5 percent per year. Previously, the MSME tax rate was set at 1 percent per year. The new MSME tax rate is one of the four tax incentive policies set by the government. Since taxes are one of the largest state revenues and MSMEs are one of the great potentials in state revenue, in this case, based on the background described, the purpose of this research is to determine the Effect of Tax Reduction on MSMEs and Tax Sanctions on Compliance with Tax Obligations for MSMEs in Kampoeng Shoes in Sidoarjo. The population of this study are all Micro, Small and Medium Enterprises (MSMEs) in Kampoeng Shoes Sidoarjo who have registered and have business permits. The population consists of 133 MSMEs. In this study, multiple linear regression analysis was used because in this study there was one dependent variable and more than one independent variable. Based on the discussion that has been carried out in the previous chapter, the following conclusions are drawn: Reduction of MSME taxes has a positive and significant impact on the level of taxpayer compliance of Micro, Small and Medium Enterprises (MSMEs) in Kampoeng Shoes, Sidoarjo. Tax sanctions have a positive and significant impact on the level of compliance of taxpayers with Micro, Small and Medium Enterprises (MSMEs) in Kampoeng Shoes Sidoarjo